Digital storytelling in health education: an example for the role of vegetables in children’s diet - Gousiou, Anthi; Kordaki, Maria (Συνέδρια της Ελληνικής Επιστημονικής Ένωσης Τεχνολογιών Πληροφορίας & Επικοινωνιών στην Εκπαίδευση, 2022)
This paper describes an educational narrative based approach for the learning of nutrition and food safety concepts by preprimary, primary and secondary educational level. Ten essential topics about Food Safety and Nutrition for children and adolescents have been identified which were employed by 10 groups of educational digital stories. The design of the aforementioned digital stories takes advantage of the Ed-W model which is presented in this paper, while an example of a specific digital story referring to the essential role of vegetables in children’s diet is also demonstrated. Finally, possible ways of use of the digital story in the classroom are discussed.